A randomized, double‐blind, placebo‐controlled, phase II clinical trial to investigate the efficacy and safety of oral DA‐1229 in patients with type 2 diabetes mellitus who have inadequate glycaemic control with diet and exercise. Issue 3 (5th December 2014) - Jung, Chang Hee; Park, Cheol‐Young; Ahn, Kyu‐Joeng; Kim, Nan‐Hee; Jang, Hak‐Chul; Lee, Moon‐Kyu; Park, Joong‐Yeol; Chung, Choon‐Hee; Min, Kyung‐Wan; Sung, Yeon‐Ah; Park, Jeong‐Hyun; Kim, Sung Jin; et al.
Abstract Background DA‐1229 is a novel, potent and selective dipeptidyl peptidase‐4 (DPP‐IV) inhibitor that is orally bioavailable. We aimed to evaluate the optimal dose, efficacy and safety of DA‐1229, in Korean subjects with type 2 diabetes mellitus suboptimally controlled with diet and exercise. Methods We enrolled 158 patients (mean age, 53 years and a mean BMI, 25.6 kg/m2). The mean baseline fasting plasma glucose level, HbA1c and duration of diabetes were 8.28 mmol/L, 7.6% (60 mmol/mol) and 3.9 years, respectively. After 2 or 6 weeks of an exercise and diet program followed by 2 weeks of a placebo period, the subjects were randomized into one of four groups for a 12‐week active treatment period: placebo, 2.5, 5 or 10 mg of DA‐1229. Results All three doses of DA‐1229 significantly reduced HbA1c from baseline compared to the placebo group (−0.09 in the placebo group vs. −0.56, −0.66 and −0.61% in 2.5, 5 and 10‐mg groups, respectively) but without any significant differences between the doses. Insulin secretory function, as assessed by homeostasis model assessment β‐cell, the insulinogenic index, 2‐h oral glucose tolerance test (OGTT) C‐peptide and post‐OGTT C‐peptide area under the curve (AUC)0–2h, significantly improved with DA‐1229 treatment. The incidence of adverse events was similar between the treatment groups and DA‐1229 did not affect body weight or induce hypoglycaemic events. Conclusions DA‐1229 monotherapy (5 mg for 12 weeks) improved HbA1c, fasting plasma glucose level, OGTT results and β‐cell function. This drug was well tolerated in Korean subjects with type 2 diabetes mellitus. © 2014 The Authors. Diabetes/Metabolism Research and Reviews published by John Wiley & Sons, Ltd.